The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.exer.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Corneoscleral stiffening increases IOP spike magnitudes during rapid microvolumetric change in the eye

Abstract: Factors governing the steady-state IOP have been extensively studied; however, the dynamic aspects of IOP are less understood. Clinical studies have suggested that intraocular pressure (IOP) fluctuation may be associated with glaucoma risk. This study aims to investigate how stiffening of corneoscleral biomechanical properties affects IOP spikes induced by rapid microvolumetric change. Porcine eyes (n = 25 in total) were subjected to volumetric infusions before and after external treatment of a circular area (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 44 publications
3
25
0
Order By: Relevance
“…Hence, the corneal stiffness growth, concurrent with the IOP raise, prevents tissue ability to deform (represented by CPA) but also causes an increase in the amplitude of IOP changes (represented by OPAp). These findings are in agreement with a study by Clayson et al [20] on porcine eyes, which showed that the induced corneal stiffening, obtained by crosslinking treatment, and the IOP rise significantly impact the magnitude of IOP spikes. In human studies, the positive correlation between IOP and OPA has been also reported in healthy subjects [58] as well as in patients with ophthalmic diseases [7,19] showing increased mechanical resistance of the ocular wall at high IOP.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Hence, the corneal stiffness growth, concurrent with the IOP raise, prevents tissue ability to deform (represented by CPA) but also causes an increase in the amplitude of IOP changes (represented by OPAp). These findings are in agreement with a study by Clayson et al [20] on porcine eyes, which showed that the induced corneal stiffening, obtained by crosslinking treatment, and the IOP rise significantly impact the magnitude of IOP spikes. In human studies, the positive correlation between IOP and OPA has been also reported in healthy subjects [58] as well as in patients with ophthalmic diseases [7,19] showing increased mechanical resistance of the ocular wall at high IOP.…”
Section: Discussionsupporting
confidence: 93%
“…In turn, the corneal mechanical resistance influences IOP fluctuations, e.g. Ocular Pulse Amplitude (OPA) and IOP spikes, as it has recently been proven in both in-vivo [7,19] and exvivo studies [20].…”
Section: Introductionmentioning
confidence: 99%
“…4). This difference can be explained by the known nonlinear mechanical behavior of the cornea, 33,34 which manifests as a more compliant response at lower IOP and a stiffer response at higher IOP. It is noted that the effect of baseline IOP on ocular pulse-induced corneal strains was not linear (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the study of Eliasy, neither bIOP or CCT were signi cantly correlated with SSI 8 , but SSI was found to be positively correlated with IOP. It was not surprising, since SSI re ected the corneal stiffness, and IOP measurement was affected by corneal stiffness 10,34 . While it was emphasized that bIOP can exclude the in uence of corneal thickness and age on intraocular pressure measurement 35 , and can re ect more accurate intraocular pressure [36][37][38] .…”
Section: Resultsmentioning
confidence: 99%
“…However, since cornea is consist of a viscoelastic material, and its stress-strain behavior of biological tissue is nonlinear 6,7 , the cornea shows the biomechanical properties of changes while under different intraocular pressure load. It is always a di cult problem to evaluate corneal biomechanics without the in uence of intraocular pressure in vivo [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%